Homomorphic Encrypted Algorithms to Achieve Security in Cloud Computing - Talasila Sasidhar, Mannam Bhargavi, Pavuluri Uma Maheswari, Mogallapalli Sai Sushmitha (International Journal of Control and Automation, 2020)
Cloud computing is an emerging technology and the use of cloud computing offers many benefits. In cloud we can store large amount of data. But while storing data in cloud we bother about security. There are many security related algorithms in cloud computing. In other algorithms like Hybrid algorithm, AES and DES we need to provide two keys: Public key and Private key. To perform any operations on data in above algorithms we need to decrypt data. While Decryption if we know the keys then we can hack the data easily. So there may be a chance of losing the data using these algorithms. So we consider Homomorphic Encryption algorithm because homomorphic encryption algorithm does not require any keys to perform operations on data.In other algorithms our data will be stored in the cloud but encoded data will be stored in the cloud by using the homomorphic encryption algorithm. If any attack occurs also our data will be secure. Homomorphic Encryption is divided into Single and Fully Homomorphic Encryption.